1996
DOI: 10.1364/ao.35.001069
|View full text |Cite
|
Sign up to set email alerts
|

Conditional-sampling spectrograph detection system for fluorescence measurements of individual airborne biological particles

Abstract: We report the design and operation of a prototype conditional-sampling spectrograph detection system that can record the fluorescence spectra of individual, micrometer-sized aerosols as they traverse an intense 488-nm intracavity laser beam. The instrument's image-intensified CCD detector is gated by elastic scattering or by undispersed fluorescence from particles that enter the spectrograph's field of view. It records spectra only from particles with preselected scattering-fluorescence levels (a fiber-optic-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Due to the fact that certain amino acids (principally tryptophan and tyrosine) fluoresce when excited near their absorption peaks in the ultraviolet (UV) region of the spectrum, a strong particle fluorescence signal indicates the presence of biological material since these amino acids occur in nearly all proteins. Therefore this spectroscopic characteristic was used to indicate the presence of biological aerosols (Seaver et al 1998;Faris et al 1997;Nachman et al 1996), and the SPFA provides both a total aerosol particle count rate and a biological particle count rate. For sizing, both the SPFA and the Met One instruments utilize the particles' optical scattering cross section to indicate size.…”
Section: Monitoring Site and Instrument Suitementioning
confidence: 99%
“…Due to the fact that certain amino acids (principally tryptophan and tyrosine) fluoresce when excited near their absorption peaks in the ultraviolet (UV) region of the spectrum, a strong particle fluorescence signal indicates the presence of biological material since these amino acids occur in nearly all proteins. Therefore this spectroscopic characteristic was used to indicate the presence of biological aerosols (Seaver et al 1998;Faris et al 1997;Nachman et al 1996), and the SPFA provides both a total aerosol particle count rate and a biological particle count rate. For sizing, both the SPFA and the Met One instruments utilize the particles' optical scattering cross section to indicate size.…”
Section: Monitoring Site and Instrument Suitementioning
confidence: 99%
“…These can be divided into three groups. The first group includes trials and studies to design and test an instrument capable of differentiating between biological and non biological aerosols such as a Fluorescence Spectrum Analyser and an Ultraviolet Aerodynamic Particle Sizer (UVAPS) (Brosseau et al, 2000;Chen et al, 1996;Hariston et al, 1997;Hill et al, 1995;Ho et al, 1999;Kaye et al, 2000;Nachman et al, 1996;Pan et al, 2003;Pinnick et al, 1998;Pinnick et al, 1995). The second group of studies aimed at designing and testing an instrument with the capability to characterise particle composition in order to discriminate between the bioaerosols themselves (Cheng et al, 1999;Pan et al, 1999;Seaver et al, 1999;Sivaprakasam et al, 2004;Weichert et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing concern on biological contamination of indoor environments, the importance of rapid monitoring of bioaerosols increases. Previous studies reported the feasibility for rapid detection of bioaerosols using modified Raman facility (Sengupta et al, 2005) or laser light source and fluorescence measurement system (Nachman et al, 1996;Hairston et al, 1997). The system developed by Hairston et al (1997) was improved into UV-APS (ultraviolet aerodynamic particle sizer spectrometer) which is a commercial instrument for realtime, continuous monitoring of airborne particles and viable airborne microorganisms.…”
Section: Introductionmentioning
confidence: 99%